Attitudes and practices in the management of attention deficit hyperactivity disorder among Brazilian pediatric neurologists who responded to a national survey: a cross-sectional study - Nunes, Marina Estima Neiva; Zuanetti, Patricia Aparecida; Hamad, Ana Paula Andrade (São Paulo Medical Journal, 2023)
BACKGROUND: Attention deficit hyperactivity disorder (ADHD) has a prevalence of 5.3% among children and adolescents. It is characterized by attention deficit, hyperactivity, and impulsivity. OBJECTIVE: We aimed to conduct a survey involving pediatric neurologists in the management of ADHD and compare the results with the current literature and guidelines. DESIGN AND SETTING: Descriptive analytical study of a virtual environment, was used Test of equality of proportions for comparison between two groups of pediatric neurologists (working as specialists for > 6 versus ≤ 6 years), with a significance level of P = 0.05. METHODS: This cross-sectional study used a virtual questionnaire covering the steps in the diagnosis and treatment of children with ADHD. The inclusion criteria were professionals who had completed their residency/specialization in pediatric neurology and clinical neurologists working in pediatric neurology. RESULTS: Among the 548 electronic invitations sent, 128 were considered valid. For all participants, the diagnosis was clinically based on the disease classification manuals. Combination treatment promotes improvement of symptoms (96.9%). Among psychostimulants, short-acting methylphenidate was the most commonly prescribed medication (85.2%). Headache was the most common side effect (77.3%). Altogether, 73.4% of the participants requested laboratory tests, 71.1% requested an electrocardiogram, and 42.2% requested an electroencephalogram. Pediatric neurologists working as specialists for ≤ 6 years had more frequent referrals to psycho-pedagogists for diagnosis (P = 0.03). CONCLUSIONS: The participants complied with clinical guidelines, emphasizing the relevance of diagnostic manuals and treatment guidelines for an eminently clinical situation and enabling uniformity in quality treatment.